Effectiveness of COVID-19 vaccines against SARS-CoV-2 variants of concern in real-world: a literature review and meta-analysis. Issue 1 (31st December 2022) - Shao, Weihao; Chen, Xiaorui; Zheng, Caifang; Liu, Haoshuang; Wang, Gaili; Zhang, Bowen; Li, Zhiyuan; Zhang, Weidong
ABSTRACT: Knowing vaccine effectiveness (VE) against variants of concern (VOCs) in the real-world setting is essential for public health decision-making. A systematic landscape of the VE against a series of clinical outcomes caused by the VOCs in the real-world setting is needed. We systematically searched for studies that evaluated VE against VOCs in the real-world setting and collected individual data. We identified 113 studies meeting the eligibility criteria. We found full vaccination provided strong protection against each clinical outcome with summary VE ranging from 86.8% to 96.0% Alpha, moderate protection against infection caused by Beta, Gamma and Delta with summary VE ranging from 70.9% to 72.8%, strong protection against severe disease caused by Delta with summary VE ranging from 84.9% to 90.3%, limited protection with summary VE of 23.5% (95% CI, 17.0–29.5) against infection and moderate protection with summary VE ranging from 56.5% to 82.4% against severe diseases caused by Omicron. Booster vaccination can provide a substantial improvement in protection against Delta and Omicron, but not as much as the Delta. The meta-regression analysis showed that the VE against the Omicron wanned over time, and the VE against hospitalization declined relatively slowly, compared to against infection. Those findings supported the need for public health measures, increasing booster vaccination coverage in response to current and new infectious waves driven by variants and developing broadly protective vaccines to confront virus evolution.